Beyond social capital: Structural barriers and digital adaptation in Community-Based Tourism at Coban Jahe, Malang Regency - Nida Fadlia (Digital Theory, Culture & Society, 2026)
This study aims to analyze the dynamics of digital adaptation in Community-Based Tourism management by examining the interaction between structural constraints and social capital at Coban Jahe Tourism, Malang Regency. A descriptive qualitative approach was employed through observation, semi-structured interviews, and documentation. The data were analyzed using Anthony Giddens’ structuration theory and Robert Putnam’s concept of social capital to understand the relationship among structure, agency, and the community’s adaptive capacity. The findings indicate that digital adaptation remains at a stage of partial transition, where digital media have been introduced but have not yet been integrated into a sustainable tourism management strategy. Structural constraints, including limited electricity supply, inadequate internet access, insufficient training opportunities, and weak institutional support, restrict the managers’ capacity to develop digital innovation. Meanwhile, social capital, manifested in internal solidarity, trust, and collective participation, contributes to maintaining the continuity of tourism management but has not been sufficient to foster digital transformation due to weak external networks. This study demonstrates that the digitalization of Community- Based Tourism is a social process shaped by the interplay of structural conditions, available resources, and the configuration of community social capital.